DEVELOPMENT OF A MOBILE APPLICATION FOR A SOFTWARE SYSTEM TO MANAGE A DIGITAL PET ID CARD - SOLOVEI , ILLIA; VOROCHEK, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work presents an analysis of competitors and the stages of development for a mobile application that includes features such as a passport, medical card, activity tracking, and a bulletin board for lost animals. The advantages and disadvantages of existing applications are discussed, with a detailed description of their functionalities. The software system offers a multifunctional solution that allows users to obtain a comprehensive electronic document about their animals, with the ability to register various species and breeds. After analyzing the software tools, the programming language Dart and the Flutter framework were chosen for developing the mobile application, ensuring execution speed and optimization for iOS interfaces using the Cupertino UI library. This allows for the creation of a high-performance and aesthetically pleasing user interface that looks harmonious on Apple devices. The system implements advanced features for interacting with the server side via the Django REST Framework, including the ability to track lost animals with geolocation data. The software system combines the functionality of several applications into one integrated solution, making it convenient and universal for a wide range of users. Key advantages of the system include support for multimedia data, interaction through QR codes, and integration with global mapping services. The paper presents elements of the mobile application interface.
Keywords: software system; mobile application; passport; digital id card; pets; Flutter; iOS; Dart